Pengendalian lipas jerman (Blattella germanica Linnaeus) dengan menggunakan attractive toxic sugar baits: Control of the german cockroach (Blattella germanica Linnaeus) by using attractive toxic sugar baits - Khairi, Fahmi; Hadi, Upik Kesumawati; Amin, Akhmad Arif (Jurnal Entomologi Indonesia, 2023)
The use of attractive toxic sugar baits (ATSB) is a novelty in vector and residential pest control. This study aims to determine the concentration of sugar bait that is able to attract the german cockroach Blattela germanica Linnaeus, and to determine the effectiveness of various types of toxic substances as an ATSB to control german cockroaches. This method is based on the behavior of adult insects that eat sugars from sources that contain toxic materials and will ultimately kill the insects. The types of toxic materials used in this study were inorganic insecticides (boric acid), pyrrole (chlorefenapir), neonicotinoids (dinotefuran), and pyrethroids (permethrin and deltamethrin). The results showed that an attractive sugar bait for german cockroach was 5% sucrose. ATSB with 25% boric acid toxic material caused 46.25% of cockroach mortality, and 0.12% chlorfenapir caused 70% of cockroach mortality 24 hours after treatment. Furthermore, ATSB with dinetofuran 0.08% and deltamethrin in various concentrations caused the highest cockroach mortality (100%), while permethrin caused cockroach mortality which was lower than ATSB with other toxic materials at the same time of observation. The conclusions of this study provide basic information about the use of ATSB and its potential in controlling the german cockroach in Indonesia.